Pseudo-pseudo Meigs' syndrome: a rare presentation of systemic lupus erythematosus - G. Tansir; P. Kumar; A. Pius; S.K. Sunny; M. Soneja (PAGEPress Publications, 2019)
Systemic lupus erythematosus (SLE) is a chronic inflammatory multisystem autoimmune disease. Ascites when associated with pleural effusion and raised CA-125 levels in SLE patient, is known as pseudo-pseudo Meigs' syndrome (PPMS). This is the case of a 22-year-old lady who presented with complaints of abdominal distension for one month and had a history of spontaneous abortion in the past. Abdominal imaging did not reveal any tumor and after extensive workup a diagnosis of PPMS was made. She was successfully treated with steroids, hydroxychloroquine and cyclophosphamide.